Performance of Public-Private Partnerships in delivering Education services: The Case of Universal Secondary Education Policy Implementation in Uganda - Barungi, Mildred; Wokadala, James; Kasirye, Ibrahim (Advances in Social Sciences Research Journal, 2015)
After implementing the Universal Primary Education policy for 10 years, Uganda initiated the Universal Secondary Education (USE) policy in 2007. The objective of the USE initiative was to equitably increase access to secondary education. The policy is implemented by public secondary schools as well as through a Public-Private Partnership (USE PPP) between the Ministry of Education and Sports and selected private secondary schools—mainly in sub counties without any public secondary schools. Within the USE PPP, the government provides a subsidy (capitation grant) to private schools to enrol UPE graduates. In this paper, we adopt the integrated framework for assessing public-private partnerships to examine the workings and performance of the USE PPP. The focus on USE PPP is due to the fact that this type of arrangement in delivering education services never existed prior to the USE policy. Based on 2013 survey findings, the USE PPP is performing moderately well in terms of good accountability, relevance, effectiveness, impact and participation. However, the USE PPP is performing poorly in terms of efficiency and sustainability. The paper has documented the major challenges faced by the USE PPP and proposed specific actions that can improve and sustain the impact of USE policy under PPP framework.